Phytochemical Screening and Evaluation of Antioxidants and Membrane Stabilizing Activities of Boehmeria glomerulifera Miq. Leaf (Bangladesh Pharmaceutical Journal, 2026)
The plant Boehmeria glomerulifera is native to Bangladesh which is used by traditional healers to treat a variety of illnesses. Therefore, we aimed to meticulously investigate the therapeutic potential such as antioxidant and membrane stabilizing activities of the leaf extract of this medicinal plant. Ethanol was used to extract the coarse leaf powder at room temperature. Chloroform-soluble and n-hexane-soluble fractions were obtained by solvent-solvent partitioning. Antioxidant potential was measured by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method, and the extractives' membrane stabilizing activity was assessed by their ability to prevent hypotonic solution-induced hemolysis of human erythrocytes. The membrane stabilizing values were presented as mean ± SE (n = 3). P values were determined using a one-way analysis of variance (ANOVA) test. Our study found the presence of organic compounds like alkaloids, flavonoids, glycosides, saponins, phenols and tannins in B. glomerulifera Miq. leaves.  The free radical scavenging and membrane-stabilizing properties of the extract increased in a dose-dependent manner. In the DPPH study, the chloroform fraction displayed the highest DPPH radical scavenging activity (IC50 = 20.13 μg/ml) compared to crude ethanol extract and its n-hexane fraction. The crude ethanol and fractionated n-hexane extracts revealed considerable scavenging activity (IC50 value: 55.80 µg/ml, 72.41 µg/ml, respectively). The chloroform fraction displayed 75.9  ±  0.252% inhibition of hemolysis of RBC at high concentrations of the extract. The crude ethanol extract and its fraction n-hexane showed inhibition of hemolysis by 29.85 ± 0.546% and 31.67 ± 0.319%, respectively, as compared to 85.99 ± 0.176% demonstrated by the standard, acetyl salicylic acid. The study found that the ethanol of B. glomerulifera and its fractions exhibit moderate to strong membrane stabilizing and notable antioxidant properties. However, further investigation is still required to isolate, characterize the phytoconstituent and determine their underlying mechanism of action of the pharmacological activities.Bangladesh Pharmaceutical Journal 29(1): 8-15, 2026 (January)